2002
DOI: 10.1590/s0034-70942002000200006
|View full text |Cite
|
Sign up to set email alerts
|

Tempo de latência e duração do efeito do rocurônio, atracúrio e mivacúrio em pacientes pediátricos

Abstract: RESUMO (T 75 ) and recovery time (T 25-75

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The use of reversal agent after administration of mivacurium in normal patients is not necessary due to the rapidity of spontaneous recovery [5]. In addition, mivacurium is considered to cause mild to moderate histamine release, but its release is less in children as compared to adults [6]. Because of its rapid onset, short duration of action, lack of accumulation, short recovery, and relative lack of adverse effects, mivacurium was chosen for cases of short duration and pediatric surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The use of reversal agent after administration of mivacurium in normal patients is not necessary due to the rapidity of spontaneous recovery [5]. In addition, mivacurium is considered to cause mild to moderate histamine release, but its release is less in children as compared to adults [6]. Because of its rapid onset, short duration of action, lack of accumulation, short recovery, and relative lack of adverse effects, mivacurium was chosen for cases of short duration and pediatric surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic searches yielded 6345 potentially relevant trials, of which 71 (48 RCTs and 23 CCTs) eligible research papers (Figure 1 and Table S1) were identified, encompassing 4319 in the large majority ASA I‐II pediatric participants in 232 study arms 43–112 . We incorporated three RCTs that enrolled only a few ASA III patients 62,64,83 .…”
Section: Resultsmentioning
confidence: 99%
“…For the comparative outcome analysis of t25, a 26‐node treatment network was produced from 48 studies (41 RCTs and 7 CCTs) with 164 study arms, including 3224 pediatric participants 43–90 …”
Section: Resultsmentioning
confidence: 99%